A meta-analysis reveals mostly neutral influence of scattered trees on pasture yield along with some contrasted effects depending on functional groups and rainfall conditions - Rivest, David; Paquette, Alain; Moreno, Gerardo; Messier, Christian (Agriculture, Ecosystems & Environment, 2013)
Scattered trees occurring throughout farmland matrix are prominent features of many human-dominated landscapes around the world, especially in livestock grazing systems. They are keystone structures that may play important roles in maintaining ecosystem functions, services, and farmland biodiversity. However, scattered trees in agricultural landscapes are declining worldwide due to intensive land use. They are often perceived by farmers as having negative impacts on agricultural production. Large-scale assessments in different biomes of agricultural yield in scattered tree ecosystems remain rare. Filling this knowledge gap may help improve decision-making regarding the value of scattered trees in agricultural landscapes. Using meta-analysis, we found that, across four tree functional groups (deciduous, Eucalyptus, N2-fixing, evergreen oak), mature scattered trees do not compromise pasture yield. The sign and magnitude of scattered tree effects on pasture yield did vary, however, among tree functional groups and according to precipitation levels. Our study suggests that, as drought pressure increases abiotic stress, tree facilitation by N2-fixing trees, and competition by Eucalyptus, will become the more common interactions between scattered trees and pasture. Management options exist to conserve and restore scattered trees in agricultural landscapes, but new policies are required to support their widespread adoption by farmers.
Keywords: Abiotic stress; Agroforestry; competition; Facilitation; Tree functional groups; tree-pasture interaction